Maxillofacial Trauma at Misurata Medical Center, Libya (2020–2023) (مجلة البحوث الأكاديمية, 2026)
Background: Maxillofacial trauma remains a significant health burden in both developing and developed settings [3], often linked to high-velocity injuries and complex anatomical involvement. This study from the Department of Oral and Maxillofacial Surgery at Misurata Medical Center in Libya covers the period January 2020 to December 2023 and aims to evaluate the incidence, etiology, fracture patterns, associated injuries, and treatment modalities of maxillofacial fractures.Methods: A retrospective analysis of 238 patients with facial fractures was performed (2020–2023). Clinical and radiographic data were reviewed including age, sex, mechanism and etiology of injury, unconsciousness/prior first aid, anatomical fracture type, treatment modality (closed vs open reduction) and complications.Results: Road traffic accidents (RTAs) remained the highest cause of fractures (≈ 72 %) affecting primarily males (male:female ratio ≈4.2:1) and the 21–30 year age-group (≈38.3 %). The mandible was the most commonly fractured bone (≈66.8 %) with the parasymphysis region the most frequent (≈30.2 %). Associated head injury was present in ~71.4 % of patients and ~13 % had a history of unconsciousness. Open reduction and internal fixation (ORIF) was the preferred modality for mandibular fractures while mid-face fractures more often underwent closed reduction.Statistical significance: RTA vs others p